CD4+ T-cell-dependent differentiation of CD23+ follicular B cells contributes to the pulmonary pathology in a primary Sjögren’s syndrome mouse model - Sato-Fukuba, Mami; Arakaki, Rieko; Ushio, Aya; Otsuka, Kunihiro; Nagao, Ruka; Matsuzawa, Shigefumi; Tawara, Hiroaki; Tsunematsu, Takaaki; Ishimaru, Naozumi (Frontiers in Immunology, 2023)
ntroduction: Primary Sjögren's syndrome (pSS) is a systemic autoimmune disease that affects the function of exocrine glands, such as the lacrimal and the salivary glands. Extraglandular lesions and malignant lymphoma also occur during the progressive stage of pSS. We have, herein, focused on the pulmonary lesions of pSS, and have aimed clarifying their pathophysiological mechanism by comparing the glandular with the extraglandular lesions observed in a mouse model of pSS. Results: The histopathological analysis of lung tissues obtained from NFS/sld mice that have undergone neonatal thymectomy was performed. Moreover, in vivo and in vitro experiments were conducted along with immunological analyses in order to characterize the unique phenotypes of the pulmonary lesions identified in these pSS model mice. Inflammatory lesions with a bronchus-associated lymphoid tissue-like structure were identified in the lungs of pSS model mice. In addition, relative to salivary gland lesions, pulmonary lesions showed increased CD23⁺ follicular B (FB) cells. In vitro and pulmonary B cells were more readily driven to CD23+ FB cell phenotype than salivary gland B cells in pSS model mice. Furthermore, the CD23+ FB cell differentiation was found to be enhanced in a CD4+ T cell-dependent manner under a Th2-type condition in the lungs of herein examined pSS model mice. Discussion: A Th2-type response in the pSS lung may promote the progression of autoimmune lesions through an enhanced abnormal differentiation of B cells.